A Qualitative Study on Job Satisfaction of Public Information Workers - Vildan Ateş; Hatice Günay (Acta Infologica)
Organizations worldwide, in both the private and public sectors, depend on their workforce to achieve optimal productivity, resulting in enhanced organizational effectiveness. Therefore, ensuring employee job satisfaction is a necessity for every organization. This study investigates the job satisfaction of public information technology (IT) employees in Türkiye. In this study, the qualitative research method was preferred, and interviews were conducted with 10 participants using a semi-structured interview form. The data obtained from the interviews was analyzed using descriptive and content analysis techniques. The study revealed that the participants’ qualifications were compatible with their job requirements. However, it was found that their overall job satisfaction was insufficient. Furthermore, the study revealed varying perspectives on topics such as employee satisfaction with workload, salary, corporate support, commitment, work-life balance, teamwork, and attitude. The results of this study also have practical implications for managers in public institutions because they provide them with a more comprehensive understanding of the factors that contribute to job satisfaction among IT public employees. The conclusion section presents recommendations for public institution managers and decision makers to enhance the job satisfaction of IT employees in public institutions